Victim-Centered Legal Pluralism and Child Protection Governance in Addressing Sexual Violence in Aceh’s Pesantren - Rosdalina Bukido; Nurlaila Isima; Hamzah Kamma; Misbahul Munir Makka; Naylah Salsabilah Kamaru (Khazanah Hukum, 2026)
This study examines sexual violence in Aceh’s pesantren (Islamic boarding schools) through a victim-centered legal pluralism perspective, focusing on the interaction between religious authority, local sharia-based criminal law, national child protection instruments, and institutional governance. Using a juridical-sociological approach, this study draws on semi-structured interviews with twelve informants, including survivors, pesantren actors, legal actors, child protection officers, and advocates from non-governmental organizations (NGOs) in Bener Meriah and North Aceh. The interview data are complemented by documentary analysis of legal regulations, child protection reports, NGO documents, media-based case documentation, and selected legal records. The findings show that sexual violence in pesantren is enabled by hierarchical relations between kiai (pesantren leaders), ustaz (religious teachers), and santri (students), especially when takzim (reverential respect toward religious authority) develops into unquestioned obedience without accountability. The study also finds that the pre-amendment implementation of Qanun Aceh No. 6 of 2014 during the 2024 fieldwork period had strong social and religious legitimacy but remained limited in ensuring victim recovery, psychosocial assistance, restitution, educational reintegration, and post-sanction monitoring. Although national instruments such as the Child Protection Law, the TPKS Law, and PMA No. 73 of 2022 provide broader victim-centered protection norms, their implementation in pesantren remains weak and fragmented. Institutionally, relevant actors such as the Ministry of Religious Affairs, DP3A, UPTD PPA, law enforcement agencies, NGOs, and pesantren administrators do not yet operate within an integrated case-management system. This study contributes to socio-legal scholarship by arguing that child protection in pesantren requires not only legal reform, but also mandatory safeguarding governance, integrated referral mechanisms, and enforceable institutional accountability.